Group Medical Visits and Microfinancial Intervention for Patients with Diabetes or Hypertension in Kenya - Vedanthan, Rajesh (J Am Coll Cardiol, 2021)
BACKGROUND: Incorporating social determinants of health into care delivery for chronic diseases is a priority. OBJECTIVES: Evaluate the impact of group medical visits and/or microfinance on blood pressure reduction. METHODS: We conducted a cluster randomized trial with four arms and 24 clusters: 1) usual care (UC); 2) usual care plus microfinance (MF); 3) group medical visits (GMV); and 4) GMV integrated into MF (GMV-MF). The primary outcome was one-year change in systolic blood pressure (SBP). Mixed-effects intention-to-treat models were used to evaluate the outcomes. RESULTS: 2890 individuals (69.9% women) were enrolled (708 UC, 709 MF, 740 GMV, and 733 GMV-MF). Average baseline SBP was 157.5 mmHg. Mean SBP declined −11.4, −14.8, −14.7, and −16.4 mmHg in UC, MF, GMV, and GMV-MF, respectively. Adjusted estimates and multiplicity-adjusted 98.3% confidence intervals showed that, relative to UC, SBP reduction was 3.9 mmHg (−8.5,0.7), 3.3 mmHg (−7.8, 1.2), and 2.3 mmHg (−7.0, 2.4) greater in GMV-MF, GMV, and MF, respectively. GMV and GMV-MF tended to benefit women, and MF and GMV-MF tended to benefit poorer individuals. Active participation in GMV-MF was associated with greater benefit. CONCLUSIONS: A strategy combining GMV and MF for individuals with diabetes or hypertension in Kenya led to clinically meaningful SBP reductions associated with cardiovascular benefit. Although the significance threshold was not met in hypothesis testing, confidence intervals for GMV-MF were consistent with impact ranging from substantive benefit to neutral effect. Incorporating social determinants of health into care delivery for chronic diseases has potential to improve outcomes.